El Excentrico, 1959-04-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
April 5, 1959 [5 de abril de 1959]. Ano 9, No. 15. Cover contains a photo of Johnny Hernanez and his son, Johnny Hernandez Jr., a lightweight boxer who became a Golden Gloves Champion prior to this issue's release. Both men were holding up a robe that's deisgned for a Golden Gloves Champion. The headline reads, "Johnny Hernandez Jr. lightweight doivision. Golden Gloves Champion